Spatial–Temporal Ontology of Indicators for Urban Landscapes - Francesco Sica; Pierfrancesco De Paola; Francesco Tajani; Endriol Doko (Land)
Urban development is increasingly scrutinized for its sustainability from an economic, social, and environmental viewpoint. This study emphasizes how important indicators are in capturing the complexity of urban settings when assessing urban landscapes and making sure that comprehensive development plans incorporate all these aspects. The work aim is to forward the investigation of the ontology of indicators related to urban sustainability, specifically, a framework for spatial and temporal analysis and an attempt to align terminology with the sustainability indicators of the ISO spectrum. The methodology encompasses three main phases: a systematic review of sustainability indicators from the scientific literature across various territorial scales; the mapping of individual indicators to their appropriate spatial–temporal measurement ranges; and the alignment of these spatially and temporally specific indicators with ISO standards. Focusing on the Italian context, this study establishes an ontological spatial–temporal framework. It analyzes ISO indicators that can be managed in Italian spatial settings. The main objective of this part of the research is to select through a critical analysis the most frequent indicators in order to be able to make an alignment and define those that aim more at the goals of the 2030 Agenda on sustainability. This innovative approach enhances urban issue awareness and supports informed decision-making by demonstrating how sustainability indicators can be effectively utilized in downscaling strategies to create a policy for the practical use of indicators.